Multivessel versus culprit-only PCI in STEMI patients with multivessel disease: meta-analysis of randomized controlled trials. (25th November 2020) - Feistritzer, H; Jobs, A; De Waha-Thiele, S; Eitel, I; Freund, A; Abdel-Wahab, M; Desch, S; Thiele, H
Abstract: Background: Previous randomized controlled trials (RCTs) indicated a benefit of multivessel percutaneous coronary intervention (PCI) compared to culprit vessel-only PCI in ST-elevation myocardial infarction (STEMI) without cardiogenic shock. Purpose: To perform a pairwise meta-analysis of RCTs, already including the recently published COMPLETE (The Complete versus Culprit-Only Revascularization Strategies to Treat Multivessel Disease after Early PCI for STEMI) trial, comparing multivessel PCI and culprit vessel-only PCI in STEMI patients without cardiogenic shock. Methods: We searched MEDLINE, Cochrane Central Register of Controlled Trials, and Embase for randomized controlled trials (RCTs) comparing multivessel PCI with culprit vessel-only PCI in STEMI patients without cardiogenic shock and multivessel coronary artery disease. Only RCTs reporting mortality or myocardial reinfarction after at least 6 months following randomization were included. Hazard ratios (HRs) were pooled using random-effect models. Results: Nine RCTs were included in the final analysis. In total, 523 (8.3%) of 6, 314 patients suffered the combined primary endpoint of death or non-fatal reinfarction. This primary endpoint was significantly reduced with multivessel PCI compared to culprit vessel-only PCI (HR 0.63, 95% confidence interval [CI] 0.43–0.93; p=0.03). This finding was driven by a reduction of non-fatal reinfarction (HR 0.64, 95% CI 0.52–0.79; p=0.001), whereas no significant reduction of all-cause death (HR 0.77, 95% CI 0.44–1.35; p=0.28) or cardiovascular death (HR 0.64, 95% CI 0.37–1.11; p=0.09) was observed. Conclusion: In STEMI patients without cardiogenic shock multivessel PCI reduced the risk of death or non-fatal reinfarction compared to culprit vessel-only PCI. Funding Acknowledgement: Type of funding source: None